1911
DOI: 10.1093/infdis/8.1.66
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Reactions of the Vegetable Proteins I. Anaphylaxis

Abstract: SYNOPSIS.2. HISTORICAL. a) THE PRECIPITIN REACTION AND VEGETABLE PROTAINS.Kowarski' seems to have been the first to report (July 4, 1901) the observation of precipitins for vegetable proteins. He immunized rabbits with solutions of noncoagulable proteins from wheat flour, and obtained a precipitin for a saline extract of wheat flour. The immune serum also gave a distinct, but less heavy precipitate with extracts of the seeds of peas, rye, and barley, but not with an extract of the seeds of oats. From his obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

1934
1934
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(62 citation statements)
references
References 1 publication
3
59
0
Order By: Relevance
“…The other study was conducted on the general population and showed that consumption of 2 g of protein from peanut or egg-white per week from the age of 3 months was associated with a lower prevalence of these respective allergies than was less consumption [16]. These findings agree with observations from studies in experimental animals; oral tolerance is induced to proteins fed in quite large amounts, while feeding miniscule amounts of foreign proteins may instead result in sensitization and allergy [17,18]. …”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The other study was conducted on the general population and showed that consumption of 2 g of protein from peanut or egg-white per week from the age of 3 months was associated with a lower prevalence of these respective allergies than was less consumption [16]. These findings agree with observations from studies in experimental animals; oral tolerance is induced to proteins fed in quite large amounts, while feeding miniscule amounts of foreign proteins may instead result in sensitization and allergy [17,18]. …”
Section: Introductionsupporting
confidence: 71%
“…Dietary proteins normally induce antigen-specific active immune tolerance, termed oral tolerance, as observed in experimental animals [44,45] as well as in humans [46]. Animal experiments have shown that feeding a sufficient amount of the foreign protein is required to achieve tolerance, while feeding smaller doses may instead result in increased sensitization [17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…It is essential to use a protein that is foreign to the diet for the reason that animals develop an immunity to foods they eat regularly (2). Such substances as crepitine, originally used by Richet (3) in his experiments on anaphylaxis, or 1 This work has been aided by a special grant from the American Academy of Arts and Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…Immunological anergy resulting from the introduction of antigen via the gastroin testinal tract represents the most ancient de scription of the phenomenon of experimen tally induced immunologic tolerance [1][2][3][4] interest in orally induced tolerance which has focused on determining the mecha nism^) underlying this state of anergy, as well as evaluating the effect which it has on the cellular compartment of the immune system [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%